Pembelajaran Berbasis Kearifan Lokal Nilai Pacu Jalur di SDN 014 Pulau Binjai Kecamatan Kuantan Mudik : Penelitian - Raja Dedek Syaiputra; Zaka Hadikusuma Ramadan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This article aims to analyze the implementation of local wisdom-based learning centered on the values of Pacu Jalur at SDN 014 Pulau Binjai, Kuantan Mudik District, Kuantan Singingi Regency, Riau Province. The research method employed is qualitative with a naturalistic inquiry approach, utilizing observation, interviews, and documentation as data collection techniques. The data were systematically analyzed through stages of data reduction, data presentation, and conclusion drawing, along with verification using source triangulation, technique triangulation, and time triangulation to ensure data validity. The results of the study indicate that the local wisdom values of Pacu Jalur, which include religiosity, mutual cooperation, deliberation, love for the homeland, culture, and sportsmanship, have been effectively integrated into the learning process and the daily lives of students. Consequently, it is expected that students will not only excel academically but also possess strong character and a love for their culture and homeland. This research provides important insights into the significance of integrating local wisdom into education to shape a generation that is morally upright and cares for their social and cultural environment.This is an open access article under.